Hemodynamic evaluation of the right portal vein in healthy dogs of different body weights - Sartor, Raquel [UNESP]; Mamprim, Maria Jaqueline [UNESP]; Takahira, Regina F. [UNESP]; de Almeida, Mariana F. [UNESP] (Biomed Central Ltd., 2010)
Background: Doppler ultrasonography is an important tool for evaluating hepatic portal hemodynamics. However, no study in dogs of different body weights, in the range encountered in routine clinical veterinary practice, has been reported. It can be difficult to obtain an ideal insonation angle when evaluating the main portal vein, so evaluation of the right portal vein branch has been described in humans as an alternative. The aim of this study was to analyze, through Doppler ultrasonography, the hemodynamics in the right portal vein branch in dogs of different body weights.Methods: Thirty normal dogs were divided in three groups by weight, in order to establish normal values for mean velocity, flow volume and portal congestion index of the right portal vein branch by means of Doppler ultrasonography.Results: In all dogs ideal insonation angles were obtained for the right portal vein branch. The average velocity was similar in the three groups, but the portal congestion index and the flow volume differed, showing that the weight of the dog can influence these values.Conclusion: Doppler ultrasonography for the evaluation of flow in the right branch of the portal vein could be a viable alternative, or complement, to examining the main vessel segment. This is especially so in those animals in which an ideal insonation angle for examination of the main portal vein is hard to obtain. In addition, the weight of the dog must be considered for the correct evaluation of the portal system hemodynamics, particularly for portal blood flow and the congestion index.